Combination of riprap and submerged vane as an abutment scour countermeasure - Fathi, Abazar (2023)
Scour is one of the main causes of hydraulic structural failures. The present experimental study examines the use of riprap, submerged vanes, and a combination of these for scour reduction around vertical walls and spill-through abutments under clear-water conditions. Specifically, the influence of placing riprap stones with different apron shapes (geometry) and/or a group of submerged vanes of constant height and length on abutment scour was examined. The main aim is to propose the optimum apron geometry and placement of submerged vanes to (1) reduce edge failure at vertical walls and spill-through abutments; and (2) prevent shear failure at the spill-through abutment (no shear failure is observed around the vertical wall abutment). The results show that using ripraps for scour protection is more effective than submerged vanes. However, the highest reduction in scour depth was achieved when a combination of riprap and submerged vanes was used together. This arrangement can reduce the maximum clear-water scour depth by up to 54% and 39% with vertical walls and spill-through abutments, respectively. Furthermore, selecting appropriate apron scale ratios reduces the required riprap volume by up to 46% and 31% for the vertical wall and spill-through abutment, respectively. In addition, the installation of vanes increased the riprap stability and reduced edge failure in both abutments tested. Finally, using riprap aprons with proper scales ratios at the downstream side of the spill-through abutment also prevents shear failure in this zone.